Comparison of International Halal Certification Management - Zulham Zulham (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2021)
The purpose of comparing the implementation of halal certification in various countries is to compare the framework of international halal certification arrangements, as well as halal certification arrangements in Indonesia. This article compares the management of halal certification in Malaysia, Singapore, and Israel with the implementation of halal certification in Indonesia. In addition, it is related to international halal certification regulations (in certain countries), international halal certification bodies, international halal certification monitoring, and international halal certification law enforcement.